The Importance of Honey Plants In Sustainable Agriculture Management - Constanta Laura AUGUSTIN (ZUGRAVU); Maria Magdalena TUREK RAHOVEANU; Loredana DIMA; Ionica SOARE; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2020)
The aims of this paper are to analysis potential of honey plants for an intensive beekeeping. This research on biological diversity has shown that pollination is a primary service within the ecosystem that is threatened worldwide. By harnessing the potential of honey plants, in this way, more productive intensive beekeeping systems can be developed that offer the benefit of sustainable ecosystems. The place of honey bees in terms of pollination of agricultural crops should be left to the wild bees that can be introduced through specific measures within agro-ecosystems and can do the pollination of agricultural crops much better than honey bees.
Keywords: intensive beekeeping; honey plants